Conflict Resolution according to KH. Sholeh Darat: A Study of the Interpretation of Fayḍ al-Raḥmān - Aziz, Thoriqul; Badruzaman, Abad (Institut Agama Islam Negeri (IAIN) Keiri, 2022)
Sholeh Darat, born in the late 19th century, authored the Fayḍ al-Raḥmān interpretation, the first in Javanese in Indonesia. He was a respected kiai, teaching many kiai in Java. This article aims to uncover Sholeh Darat's conflict resolution method through his commentary and contributions in Indonesia. Employing a descriptive-analytical-historical approach, it reveals two significant conflict resolution strategies. Firstly, Sholeh Darat mediated conflicts between exoteric and esoteric interpreters. By incorporating both interpretations using the Sufi-ishari method, he reconciled differing viewpoints. Secondly, he resolved conflicts between sharia adherents (fuqaha) and followers of Islam Kejawen (essence). Employing sharia principles to reach mystical truths, he bridged the gap between these groups. These efforts significantly influenced Indonesia's religious landscape, particularly through his prominent students, KH. Ahmad Dahlan, founder of Muhammadiyah, and KH. Hasyim Asy'ari, founder of Nahdlatul Ulama (NU). Sholeh Darat's approach promoted religious harmony and cooperation, shaping Indonesia's religious tolerance ethos. Through his interpretations and teachings, he fostered understanding and unity among diverse religious perspectives, leaving a lasting impact on Indonesian society.